Compressive performance of masonry columns confined with highly ductile fiber reinforced concrete (HDC). (10th September 2020) - Deng, Mingke; Li, Tong; Zhang, Yangxi
Highlights: ·The effectiveness of HDC system used to confine masonry was studied. ·The HDC as binding mortar clearly improved the deformability rather than strength. ·The HDC jacket could increase both the strength and deformability. ·Analytical model was proposed for predicting strength of confined masonry. Abstract: This work presents the results of an experimental investigation on the compressive behavior of clay brick masonry columns confined with highly ductile fiber reinforced concrete (HDC). The study aims to prove the effectiveness of the proposed confinement technique and detect the efficiency of different confinement forms of HDC, including internally-placed HDC which was used as binding mortar in the joints (i.e. internal HDC mortar) and external HDC jacket. Furthermore, the effect of confinement materials is examined. Analysis of the failure mode, axial load–displacement curves, peak load and ductility reveals that internal HDC mortar could considerably improve the deformability of masonry columns. Although the external HDC jacket could increase the load carrying capacity and deformability, the detachment between the external layer and masonry substrate is observed at the post-peak stage. Contribution of cement-based mortar jacket to the masonry columns is merely enhancing the load carrying capacity rather than deformability, which was caused by its quite low tensile strength. Moreover, based on the theories of mesh-reinforced brick masonry and steel tube confined concrete, analytical models available in the literatures are adopted to predict the compressive strength of HDC systems confined masonry columns. The calculation model gives a better approximation to predict the compressive strength of confined masonry columns but should need further experimental data in the future other than those adopted in this paper to verify the accuracy and reliability.